Instilling anti-corruption characters in civic education for college students - Aksinudin, Saim; Wiyono, Subelo; Nariswari, Ayu Fitria (Universitas Negeri Yogyakarta, 2022)
Corruption is a serious problem that needs to be resolved. Many of Indonesia's assets are lost due to corruption. Many state officials were arrested because of it, and new corruption cases kept on rising. Anti-corruption education for college students has become one of the assisting measures in the anti-corruption strategy. Some studies suggest that prevention through education is the most important step to eradicate corruption. This study aimed to examine the role of Civic Education (CE) as an anti-corruption education for students. This study used a qualitative method. Data were collected through literature study, in-depth interviews, and observation. The collected data were then analyzed using Miles & Huberman's interactive model which consists of data collection, data verification, data analysis, and conclusion drawing. The results of this study show that Civic Education plays a vital role in anti-corruption education for students. In the context of higher education, this course may serve as anti-corruption education. Anti-corruption values should be delivered during the CE learning process. Anti-corruption values consist of honesty, discipline, and compliance. The results of this study can be a reference for policymakers in the field of corruption prevention.